If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying g + -13 = 5 Reorder the terms: -13 + g = 5 Solving -13 + g = 5 Solving for variable 'g'. Move all terms containing g to the left, all other terms to the right. Add '13' to each side of the equation. -13 + 13 + g = 5 + 13 Combine like terms: -13 + 13 = 0 0 + g = 5 + 13 g = 5 + 13 Combine like terms: 5 + 13 = 18 g = 18 Simplifying g = 18
| 136=8(1-2m) | | -4x-8+2x=-20 | | 17=23-t | | 1m^2+9m-5=0 | | 8w=36+4w | | -3.375=-.666x-3.833x | | 6b+7-10= | | 21+p=45 | | 2m+7+8m-3= | | 3r^2-78r+87=0 | | 6y-21-4y+27=21-3y | | 142-9x+20=7x-6 | | d+7=19 | | -35+2b+b^2=0 | | 2(-1+2x)=-9+5x | | 10x^7y^2+5xy= | | 4x+2y=576 | | 1y^2-1y=6 | | 5(x+1)+5=13-2+6x | | 3(4x+3)=2x-5(-3-x)+2 | | 6x-7=-90 | | 22=j-13 | | I-4(2x+3)=2x+6-(8x+2) | | 44+s=63 | | 5X-7Y-4X+8Y= | | 73+m=100 | | 9(x+4)=-36 | | 82+2x+(3x-17)=180 | | 7v=42+v | | 9(x-4)=-37 | | 5X-7Y-4X+7Y= | | 3+-2x=-1.5x |